i-ACT for life: a prevention module featuring integrated elements of Islamic Spirituality and Acceptance and Commitment Therapy (ACT) - Practitioner's Manual - Abdul Khaiyom, Jamilah Hanum; Abdul Aziz, Amani Fadzlina; Md Rosli, Ahmad Nabil; Bahari, Che Amnah; Abdullah, Nur Sakinah Thomas (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
“How can we help our young adults to thrive during COVID-19?”